2004
DOI: 10.3923/pjn.2004.232.236
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salt Concentration on Some Characteristics in Herby Cheese

Abstract: Herby cheese is a salted traditional cheese manufactured from sheep's and cow's milk in the Eastern and Southeastern of Turkey. The aim of this study was to assess the influence of different salt concentrations (4, 5 and 6%) on the ripening characteristics of Herby cheese. Pasteurized whole cow's milk (3.7% fat) was used for Herby cheese manufacture. The cheese samples were ripened under soil at 7±1 C o for 90 days. The samples were characterized in terms of microbiological, chemical and sensory properties. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…These variations were statistically significant (p<0.05) and most probably occurred because the salting of cheeses was carried out manually, without precise quantity. The results obtained in this study confirmed earlier findings of Tarakci et al (2004) considering cheese dry salting influence on the increase in cheese dry matter.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These variations were statistically significant (p<0.05) and most probably occurred because the salting of cheeses was carried out manually, without precise quantity. The results obtained in this study confirmed earlier findings of Tarakci et al (2004) considering cheese dry salting influence on the increase in cheese dry matter.…”
Section: Resultssupporting
confidence: 92%
“…Yeasts can occur in cheese in higher number during the salting. It was noticed that higher salt content had favorable influence on yeasts and moulds growth (Tarakci et al, 2004). However, the high content of NaCl and S/M ratio in the beaten cheese caused a decrease in the yeast number.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, it was clearly observed that degradation rates of α S1 -casein and β-casein in spiceadded cheeses is higher than that of the control cheese. When similar studies are examined, in herby cheese Tarakci, Sagun, Sancak, and Durmaz (2004) and Tunçtürk, Ocak, and Köse (2014); in spiceadded white cheese Tarakçı and Deveci (2019) and Aydın (2019); in fruit-added kashar cheese Bayram (2018) found that the amount of α S1 -casein and β-casein decreased in the samples.…”
Section: Electrophoretical Casein Fractions In Cheesementioning
confidence: 97%